Preservice Elementary Teachers’ Nature of Science Courses: Explicit, Implicit, or…? - Subuh Anggoro , Santhy Hawanti , Noreen Izza Arshad , Corrienna Abdul Talib , Azmi Fitriati; Neni Hermita (International Journal of Advanced Science and Technology, 2020)
Most of preservice elementary teachers’ have misunderstood about aspects of nature of science (NoS). In fact, teachers’ understanding of NOS have an impact on learning in the classroom teaching. Purposes of this research are: (1) to know their misunderstood of NoS aspects; and (2) to make an alternative practice that improved their NoS. This research used survey method design. Beliefs about nature of science questionnaire was used as research instrument. The questionnaire currently being developed to break the ground for future cross-sectional research on the nature of science. The questionnaire taps from aspects of nature of science as knowledge, process, attitude, and social dimension. The 56-item NoS questionnaire was administered to a sample of 223 (18% male and 82% female) preservice elementary teachers. The validity of the instrument (questionnaire) used a test construct validity with expert judgment reference and the empirical validity. Data analysis used descriptive with percentage. The main findings were as follows: (1) some aspects of NOS (hypothetico-deductive testing, durable, tentative,) are more misunderstood than others (science as product of imagination and creativity, natural phenomena, social and cultural embeddedness, scientific knowledge is open to revision with the latest evidence, science affects human social life, and scientific method). The misunderstood of NoS aspect can be reduced through explicit-reflective learning, NoS Pedagogical Content Knowledges (PCK), and inquiry and natures of science, technology, and engineering (INSTE) course